In vitro effect of leptin on human cardiac contractility. (10th April 2019) - Chaban, Ryan; Buschmann, Katja; Ghazy, Ahmed; Poplawski, Alicia; Wittmann, Nadja; Beiras-Fernandez, Andres; Vahl, Christian-Friedrich
Abstract: Leptin, a hormone produced by adipose tissue, has been linked to many regulatory pathways. Its role in the complex relationship between obesity and CVD is not yet clear. The aim of the present study was to evaluate whether leptin interferes directly with cardiac function regulation, altering its contractile force character, and hence contributing to different pathological processes. Muscle samples were obtained from human atrial myocardium. Each trial included two samples from the same patient. They were simultaneously electrically stimulated under sustained perfusion to perform isometric contractions. One sample was treated with a high concentration of human recombinant leptin (1 µg/ml). The other was treated with placebo and served as a control. The exhibited contraction forces (CF) and the contraction duration (CD) after 20 min of treatment were normalised by dividing them by the values before the treatment and reported as a percentage. A total of ten successful trials were conducted. Exposure to leptin did not yield a statistically significant variation in both CF and CF. In the treatment group, CF% measured 108 (95 % CI 91, 125) % and CD% measured 95 (95 % CI 90, 101) % after 20 min. In the control group, CF% measured 105 (90 % CI 84, 126) % and CD% measured 92 (95 % CI 80, 105) % after 20 min. We concluded that leptin does not alter the contractile character of human atrial tissues, even in supraphysiological dosage. These results suggest that leptin does not play a role in short-term cardiac regulation.